Conformational dynamics of intracellular tau protein revealed by cd and saxs - Gorantla, vijay nalini; Alexander, V. Shkumatov; Chinnathambi, Subashchandrabose (Methods in Molecular Biology, 2017)
A native conformation of a protein is essential for its biological role. In certain conditions, some proteins show non-native conformations, leading to aggregation, which in turn may produce severe pathologies. Such physiological conditions are classified as protein misfolding diseases. Alzheimer’s disease (AD) is the most common form of dementia. Extracellular senile plaques formed by Amyloid β and intracellular aggregates formed by microtubule-associated protein Tau (MAPT) are the hallmarks of AD. Physiological role of MAPT is to maintain the integrity and stability of microtubules, however it tends to self-aggregate forming intracellular paired helical filaments (PHFs) during AD. MAPT is also subjected to various post-translational modifications such as phosphorylation, glycosylation, truncation, and acetylation. Being natively unfolded, MAPT is prone to full characterization at atomic level. Small-angle X-ray scattering (SAXS) is often applied in combination with other biophysical methods, like nuclear magnetic resonance (NMR), circular dichroism (CD), fluorescence spectroscopy, analytical ultracentrifugation (AUC), or dynamic light scattering (DLS) to characterize natively unfolded systems. Here we describe the practical aspects of MAPT characterization by SAXS and CD in detail as well as outline the inferred structural and functional implications.